Advancements in Physiotherapy: The Role of Medical Devices in Enhancing Rehabilitation Outcomes – A Comprehensive Review - Leslom, Awad Nasser Dafer; Alyami , Hussain Hamel Ahmad; Al salom, Muhammad Ali Muhammad; Zabarah, Saleh Hadi Saleh; Alyami , Hamad Mana O; Al Alshehi , Abdullah Saleh; Alahmari , Khalid Mari Abdullah; Alalhareth , Hadi Dafer Nasser; Almakrami, Hussain Ali Mohammed; AL Rashah, Yousef Ahmed Saleh (Journal of Ecohumanism, 2024)
Physiotherapy has evolved significantly with the integration of medical devices, transforming traditional rehabilitation practices and improving patient outcomes. This review explores advancements in medical devices, such as robotic-assisted therapy, wearable technologies, and virtual reality, highlighting their applications in enhancing mobility, pain management, and recovery speed. The study synthesizes evidence from recent clinical trials and literature, discussing the benefits, challenges, and future potential of these technologies in physiotherapy. Emphasis is placed on their role in creating patient-specific rehabilitation plans and addressing barriers to adoption, including cost and accessibility. The findings underscore the need for innovative, cost-effective solutions to broaden the impact of these advancements globally.